The challenges and opportunities for ERM post-COVID-19: Agendas for future research - Don Pagach; Monika Wieczorek-Kosmala (Journal of Risk and Financial Management, 2020)
In this paper, we examine the impact that COVID-19 has had on enterprise risk management (ERM). Guided by the origins and philosophy of ERM, we suggest an agenda for future research on ERM in a 'post-COVID-19' reality, by addressing its integrated, strategic, and value-enhancing orientation. To guide future research endeavors in ERM, which is still an evolving discipline, we present topics that would benefit from additional research attention within both risk identification and analysis, as well as the strategic dimension of ERM.
Keywords: 330; COVID-19; pandemic; enterprise risk management (ERM); risk analysis; risk reporting